"No better or worse off": Mycoplasma bovis, farmers and bureaucracy. (December 2021) - Jaye, Chrystal; Noller, Geoff; Bryan, Mark; Doolan-Noble, Fiona
Abstract: The 2017 outbreak of Mycoplasma bovis in New Zealand deeply impacted rural communities, particularly cattle farmers. In 2018, the Ministry for Primary Industries (MPI) implemented an eradication programme that involved herd testing, stock culls, restriction of stock movements, decontamination of affected farms, and compensation to farmers for losses associated with the eradication programme. New Zealand news media reported widely on the emotional trauma experienced by affected farmers and MPI was criticised for poor management of the outbreak. We interviewed nineteen farmers and farming couples affected by M. bovis in Southern New Zealand to gain insight into their experiences of the outbreak. In this paper, we present the findings pertaining to one dominant thematic: that of farmers' interactions with the bureaucracy associated with the management of the outbreak. The farm appeared to quite literally represent a site of collision between farming values of stock welfare and practical and relational forms of knowledge; and policy, regulation, compliance and technical instrumental forms of knowledge. For these reasons, Habermas' theory of lifeworld and system presented itself as a particularly salient framework for interpreting our data. Participants experienced the eradication programme as intrusive, impractical, and inhumane; while their situated local knowledge and pragmatism were ignored in favour of adherence to wasteful and inefficient bureaucratic processes that while compliant with policy, made no sense to the farmers. We suggest that biosecurity threats such as M. bovis might be more effectively managed when the bureaucracy is attentive to the rural lifeworld and responsive to the situated knowledge of farmers. Highlights: Conflict over management of New Zealand 2017 Mycoplasma bovis outbreak. "No better or worse off" policy a key site of conflict. Pragmatic situated knowledge asserted against policy and bureaucracy. Habermas' lifeworld and system provides insights into what was being contested.